Al-Battani contributions in astronomy and mathematics - Abdullatif, Mohammad Salah Aldin; Daoud, Jamal Ibrahim (IIUM Press, 2011)
This chapter is talking about one of the famous and greatest Islamic astronomers and mathematicians around the world; AI-Battani has great and significant contributions in astronomy and mathematics. In astronomy, he has astronomical observations for more than forty years. In addition, he did some corrections upon Ptolemy's results and made some new tables of the Sun and the Moon. Moreover, he determined the length of solar year. In mathematics, he innovated new relationships in trigonometric, and created a table of cotangents, and made some formulas in spherical trigonometry